2014
DOI: 10.1039/c4ay01027b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching studies of CTAB stabilized perylene nanoparticles for the determination of Cr(vi) from environmental samples: spectroscopic approach

Abstract: CTAB-PNPs are bound to dichromate ion by electrostatic interaction to form stable non-fluorescent micellar complex which is responsible for the ‘FL quenching’ of CTAB-PNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…N-MINPs were prepared by a reprecipitation method [12,28,29] in aqueous medium. A 2 mL, 1 × 10 −5 M solution of N-MI in acetone was injected directly into 50 mL water and stirred for 60 min, followed by ultrasonication for 10 min.…”
Section: Preparation Of N-methyl Isatin Nanoparticles (N-minps)mentioning
confidence: 99%
See 2 more Smart Citations
“…N-MINPs were prepared by a reprecipitation method [12,28,29] in aqueous medium. A 2 mL, 1 × 10 −5 M solution of N-MI in acetone was injected directly into 50 mL water and stirred for 60 min, followed by ultrasonication for 10 min.…”
Section: Preparation Of N-methyl Isatin Nanoparticles (N-minps)mentioning
confidence: 99%
“…The enhanced emission arising from FONs have been widely employed to sense metal ions and methods reported in the literature are of high sensitivity, special selectivity and good stability [11,12]. The past few years have witnessed a number of sensory reports on the design and synthesis of functionalized FONs for the detection of metal ions [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Here in, SDS capped RUBNPs exhibited J-type aggregates or head-to-tail structure that usually showed fluorescence with an intensity that fairly often exceeded that of the monomer rubrene solution in THF. According to the exciton theory of Kasha et al [4][5][6] in J aggregates, only transitions to the low energy states of the exciton band are allowed and, as a consequence, J-aggregates are characterized by a high fluorescence quantum yield. Fluorescence spectroscopy suggested that the SDS-RUBNPs existed in equilibrium with molecular rubrene in solution as its characteristic bands are not appeared in fluorescence spectrum of nano dispersion.…”
Section: Fluorescence Properties Of Rubrene and Sds Cappedmentioning
confidence: 87%
“…Among them, polycyclic aromatic hydrocarbons, such as pyrene, anthracene andperylene are frequently employed for sensor applications. [4][5][6] The investigation of nanoparticles and microcrystals of such organic molecular materials is currently a rapidly growing field.…”
Section: Introductionmentioning
confidence: 99%